PERILAKU PEMILIH MENJELANG PILKADA SERENTAK 2015 DI KOTA SEMARANG - Pradhanawati, Ari; Farida, Naili; Abdulrahman, Wahid; Hanura, Marten (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Indonesian political dynamics over the last 16 years since the Reformation movement initiated, the building shows the fragility of the Indonesian political experience. This can be seen how the level of community participation in the General Election in the Reformation era tend to decline until today. Election deemed not produce leaders who provide real change. This is exacerbated by the political system characterized transactional fraud. The purpose of this study was to look at the political behavior of society and give provisions regarding political education to the public ahead of the elections simultaneously in Semarang, especially in the Village Meteseh and Mangunharjo on December 2015. In this research use several theories: theory of rational choice and the theory of political participation.